CODE MIXING IN WEBTOON COMIC SOEKIRMAN: RAMADHAN DI KAMPUNG HALAMAN AS A FORM OF JAVANESE LANGUAGE MAINTENANCE - Yashinta Farahsani; Sri Ani Puji Setiawati (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The increasing dominance of national and global languages has raised concerns about the maintenance of regional languages in multilingual societies. In response to these challenges, digital media have emerged as alternative spaces for preserving local linguistic identities. One such medium is Webtoon, a digital comic platform that enables the representation of regional languages within contemporary online communication. This study investigates code mixing in the Webtoon comic Soekirman: Ramadhan di Kampung Halaman and examines its role in maintaining the Javanese language in a digital environment. Employing a qualitative descriptive approach, the study analyzed utterances containing code-mixing phenomena involving Javanese, Indonesian, and English. The data were collected through observation and documentation techniques. The data were analyzed based on the sociolinguistic concept of code mixing (Bokamba, 1988; Muysken, 2000), while the classification of code-mixing forms followed Suwito's (1996) framework developed for the Indonesian linguistic context. The interpretation of the findings was subsequently informed by Fishman's (1991) theory of language maintenance. The findings revealed 37 instances of code mixing categorized into seven forms: basic words, affixed words, compound words, phrases, basters, reduplication, and clauses. Among these categories, basic-word code mixing was the most dominant form. The findings further demonstrate that code mixing functions not only as a communicative strategy but also as a mechanism for preserving Javanese linguistic visibility, cultural identity, and local expressions within contemporary digital discourse. The study concludes that Webtoon serves as a new domain for language maintenance by facilitating the continued use and transmission of Javanese linguistic elements to wider audiences. These findings contribute to sociolinguistic discussions on multilingual communication, digital media, and regional language preservation in the digital era.